STRATEGI KEPALA MADRASAH DALAM PENINGKATAN PRESTASI NON AKADEMIK DI MTsN 13 JOMBANG - Rahayu Ningsih; Abdullah Aminuddin Aziz (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Several non-academic achievements that have been achieved by MTsN 13 Jombang students include 3rd place in the Robotics Competition at UTM (University Technology Malaysia), 3rd place in National Badminton in 2022, and 1st Place in National Badminton (men's singles) in 2022. This research will discuss the madrasa head's strategy in improving non-academic achievements at MTsN 13 Jombang This research uses a qualitative method with a case study approach at MTsN 13 Jombang. Primary data was obtained from interviews with the madrasa head, deputy head of student affairs, extracurricular teachers, and outstanding students, while secondary data came from school documents. Data collection techniques include observation, structured and unstructured interviews, and documentation. Data analysis was carried out interactively using the Miles and Huberman method, which includes data reduction, data presentation and drawing conclusions. The results of this research show that the Headmaster of MTsN 13 Jombang has a strategy to improve student achievement through developing relevant extracurriculars, providing adequate facilities, training and developing human resources, as well as school-based management approaches and effective motivation. MTsN 13 Jombang has many non-academic achievements in the fields of sports, arts, scouts and social activities, which not only improve students' physical and social skills but also develop their character and emotional intelligence. This increase in non-academic achievement is supported by various strategies, such as extracurricular empowerment, training and coaching, collaboration with external parties, rewards and motivation, infrastructure support, a holistic approach, soft skills development, involvement of parents and the community, increasing teacher competency, and evaluation. and monitoring.